Praktik Perjodohan Online Untuk Mendapatkan Pasangan Hidup Perspektif Ulama Kabupaten Banjar - Ulya, Lina (Sharia Journal and Education Center Publishing, 2026)
Advances in communication technology have shifted the culture of introduction (ta'aruf) from conventional methods to digital platforms. This phenomenon of online matchmaking has sparked a debate about the sanctity of the value of marriage in the midst of the religious community of Banjar Regency. This research uses an empirical legal research method that aims to dissect the mechanism of online matchmaking and the construction of the thinking of local scholars. Data was collected through in-depth interviews to explore the legal basis and religious arguments of informants against the phenomenon. The results of the study show that there is a dynamic between the view of mubah as convenience (wasilah) and prudence (ihtiyath) in order to maintain the dignity of women. Online matchmaking is considered positive as long as it maintains sharia manners, data honesty, and is under the supervision of a guardian.